Tailoring the Structure of Low‐Dimensional Halide Perovskite through a Room Temperature Solution Process: Role of Ligands. Issue 6 (21st April 2021) - Yoo, Young‐Taek; Heo, Do Yeon; Bae, Sa‐Rang; Park, Jinwoo; Lee, Tae‐Woo; Jang, Ho Won; Ahn, Sang Hyun; Kim, Soo Young
Abstract: In this study, halide perovskite nanocrystals are synthesized by controlling the ligand length and amount, and investigated the effects on the change in the ligand length and amount on the shape, size, crystal structure, and optical properties of the perovskite nanocrystals. The results reveal the tendency and respective effects of amine and acid ligands on perovskite nanocrystals. The amine ligands bind directly to the perovskite nanocrystals. Consequently, the amine ligands with longer chains interfere with the aggregation of the initially formed nanocrystals, thus limiting the size of the halide perovskite nanocrystals. Similar to the amine ligands, the acid ligands directly bond with the perovskite nanocrystals; however, they are also indirectly distributed around the nanocrystals, thus affecting their structure and dispersion. Consequently, the acid ligands affect the assembly of the initially formed nanocrystals, which determine the shape and crystal structure of the nanocrystals. It is believed that the report will provide useful insight on the synthesis of halide perovskites for application in optoelectronic devices. Abstract : The role of the acid and amine ligands is identified by the trends of the changes in shape, size, and crystal structure of the perovskite nanocrystals. The reason for the effects of the acid and amine ligands and the mechanism of ligand binding on the nanocrystalline surfaces of the perovskite are investigated.